Enhancing mathematical creative thinking through the ADIRE learning model based on learning styles - Medyasari, Larasati Tiara; Zaenuri, Zaenuri; Dewi, Nuriana Rachmani; Wijayanti, Kristina (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study responds to the persistent issue of low mathematical creative thinking among students by exploring its underlying causes and examining the effectiveness of the ADIRE (Auditory, Intellectual, Repetition with Ethnomathematics) learning model when viewed from different learning styles. Method: A mixed-methods approach with a sequential exploratory design was applied. The participants were seventh-grade students. In the qualitative phase, subjects representing visual, auditory, and kinesthetic learning styles were selected purposively. The quantitative phase employed cluster random sampling to assign students into experimental and control groups. Data were gathered through tests, questionnaires, interviews, observations, and documentation, and analyzed using descriptive statistics, t-tests, and N-gain analysis. Findings: The findings reveal that students’ creative thinking ability remains uneven across learning styles. Visual learners tend to demonstrate more complete achievement of creative thinking indicators, while auditory learners generally require guidance, and kinesthetic learners show limited attainment, mainly at the basic level. The implementation of the ADIRE learning model leads to a noticeable improvement in students’ performance, reflected in higher average scores, fulfillment of minimum mastery criteria, and a moderate level of gain. Significance: These results suggest that learning models which consider students’ learning styles and incorporate ethnomathematical contexts can provide more meaningful learning experiences and contribute to the development of mathematical creative thinking in a more holistic way.